The Effect of Mulberry Fruit Juice Substitution on Nata Sensory Quality - Mauly Izzati Nabila; Sari Mustika; Anni Faridah; Rahmi Holinesti (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2025)
Mulberry plants are generally used for their leaves as silkworm feed, while their fruits are rarely used. In fact, mulberry fruit has the potential as a functional food because of its antioxidant content and high economic value. One form of processing is making nata to add variety. This study aims to determine the effect of mulberry juice substitution at concentrations of 0% (X0), 25% (X1), 50% (X2), and 75% (X3) on the sensory quality of nata including color, aroma, texture, and taste. The method used was a pure experiment with a completely randomized design (CRD), involving 50 panelists. Data were analyzed using ANOVA and Duncan's test. The results showed that 50% mulberry juice substitution (X2) significantly increased the nata color score by 2.99, and produced a slightly chewy texture with a score of 2.28 which was still preferred by panelists. Aroma and taste did not show significant differences. Based on the overall results, treatment X2 (50%) was the best treatment in producing nata with the most preferred sensory quality.